2014
DOI: 10.5114/fn.2014.45568
|View full text |Cite
|
Sign up to set email alerts
|

Original article Delayed preconditioning with NMDA receptor antagonists in a rat model of perinatal asphyxia

Abstract: A b s t r a c t Introduction: In vitro experiments have demonstrated that preconditioning primary neuronal cultures by temporary application of NMDA receptor antagonists induces long-term tolerance against lethal insults.In the present study we tested whether similar effects also occur in brain submitted to ischemia in vivo and whether the potential benefit outweighs the danger of enhancing the constitutive apoptosis in the developing brain. Material and methods: Memantine in pharmacologically relevant doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Slomka et al applied the same protocol to cultured cerebellar cells and observed an increased tolerance as well (Slomka et al, 2014). There have been significant efforts to understand how HPC/IPC confers neuroprotection via its effects on glutamate (Liu et al, 2009) and other neurotransmitters, and new experimental models are testing chemical preconditioning of NMDA receptors to reduce subsequent excitotoxic cell death (Makarewicz et al, 2014; Stetler et al, 2014; Constantino et al, 2015). In a recent study of transient cerebral ischemia and neurons in the gerbil hippocampal CA1 region, kynurenic acid immunoreactivity was maintained or even increased.…”
Section: From Hypoxia To Ischemia: Mechanism Of Neuroprotectionmentioning
confidence: 99%
“…Slomka et al applied the same protocol to cultured cerebellar cells and observed an increased tolerance as well (Slomka et al, 2014). There have been significant efforts to understand how HPC/IPC confers neuroprotection via its effects on glutamate (Liu et al, 2009) and other neurotransmitters, and new experimental models are testing chemical preconditioning of NMDA receptors to reduce subsequent excitotoxic cell death (Makarewicz et al, 2014; Stetler et al, 2014; Constantino et al, 2015). In a recent study of transient cerebral ischemia and neurons in the gerbil hippocampal CA1 region, kynurenic acid immunoreactivity was maintained or even increased.…”
Section: From Hypoxia To Ischemia: Mechanism Of Neuroprotectionmentioning
confidence: 99%
“…From these results it can be concluded that activation of NMDAR in nervous tissue may result in protection or damage depending on the localization of NMDAR, as well as on the degree of activation. Several authors indicated the beneficial effects of NMDAR antagonists, primarily MK-801 and memantine, in various models of neuron damage including hypoxia-ischemia and harmful effects of oxygen and glucose deprivation (27,28). Doeppner et al showed that acamprosate, as indirect NMDAR antagonist, exhibited neuroprotective effects if administered 12 hours before stroke, through inhibition of calpain-mediated pro-injurious signaling cascades (29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the antagonism of NMDARs in the developing brain increases constitutive apoptosis [12,24] and decreases brain weight 2 weeks after a single MK-801 injection [21]. Moreover, NMDAR antagonists interfere with thermoregulation and induce hypothermia in neonatal rats [9].…”
Section: Discussionmentioning
confidence: 99%